White Nights The Mariinsky Ballet in situ - Witchel, Leigh (Dance Books Ltd., Alton,Hampshire (UK), 2006)
The Mariinsky Ballet is seen in situ. Gergiev can wring Wagnerian drama out of the music whether it's there or not. PALABRAS CLAVE: Mariinsky's productions, Mariinsky Ballet.